(+)-9-Trifluoroethoxy-α-Dihydrotetrabenazine as a Highly Potent Vesicular Monoamine Transporter 2 Inhibitor for Tardive Dyskinesia - Wang, Wenyan; Du, Guangying; Lin, Shilan; Liu, Jing; Yang, Huijie; Yu, Dawei; Ye, Liang; Zou, Fangxia; Wang, Hongbo; Zhang, Rui; Tian, Jingwei (Frontiers in Pharmacology, 2021)
Valbenazine and deutetrabenazine are the only two therapeutic drugs approved for tardive dyskinesia based on blocking the action of vesicular monoamine transporter 2 (VMAT2). But there exist demethylated inactive metabolism at the 9 position for both them resulting in low availability, and CYP2D6 plays a major role in this metabolism resulting in the genetic polymorphism issue. 9-Trifluoroethoxy-dihydrotetrabenazine (13e) was identified as a promising lead compound for treating tardive dyskinesia. In this study, we separated 13e via chiral chromatography and acquired R,R,R-13e [(+)-13e] and S,S,S-13e [(−)-13e], and we investigated their VMAT2-inhibitory activity and examined the related pharmacodynamics and pharmacokinetics properties using in vitro and in vivo models. (+)-13e displayed high affinity for VMAT2 (Ki = 1.48 nM) and strongly inhibited [3H]DA uptake (IC50 = 6.11 nM) in striatal synaptosomes. Conversely, its enantiomer was inactive. In vivo, (+)-13e decreased locomotion in rats in a dose-dependent manner. The treatment had faster, stronger, and longer-lasting effects than valbenazine at an equivalent dose. Mono-oxidation was the main metabolic pathway in the liver microsomes and in dog plasma after oral administration, and glucuronide conjugation of mono-oxidized and/or demethylated products and direct glucuronide conjugation were also major metabolic pathways in dog plasma. O-detrifluoroethylation of (+)-13e did not occur. Furthermore, CYP3A4 was identified as the primary isoenzyme responsible for mono-oxidation and demethylation metabolism, and CYP2C8 was a secondary isoenzyme. (+)-13e displayed high permeability across the Caco-2 cell monolayer, and it was not a P-glycoprotein substrate as demonstrated by its high oral absolute bioavailability (75.9%) in dogs. Thus, our study findings highlighted the potential efficacy and safety of (+)-13e in the treatment of tardive dyskinesia. These results should promote its clinical development.